Report of a case of agenesis of the uterus and vagina. - Calderón V., Rolando (2015)
Vaginal agenesis has been recently reported in our midst and agenesis of the uterus and the upper third of the vagina is quite often. Remember that embryologically the lower two thirds of the vagina develop from the urogenital sinus, while the upper third: the uterus and fallopian develop from Muller duct.